Forget me not ebook - Soto, Julie (2023)
A wedding planner and her grumpy ex must work together to plan a celebrity event in this deliciously spicy and funny novel from Ali Hazelwood's "favorite writer."  Ama Torres is an optimistic wedding planner who doesn’t believe in marriage. But weddings? They’re amazing. Elliot Bloom is a brooding florist who hates owning a flower shop…until a certain bright-eyed, donut-loving workaholic shows up at his door. Once upon a time, they collaborated on events by day, and by night, Ama traced the intricate flower tattoos etched along his body. Then Ama shattered his heart and never spoke to Elliot again.     Now they’re working on an event that could make or break both of their careers—except neither of them has gotten over what happened two years ago. Things are not helped by the two brides, who see the obvious chemistry between Ama and Elliot and are determined to set them up, not knowing their complicated history. But as the wedding takes on a life of its own, Ama and Elliot are about to discover that some things can survive a complete catastrophe . . .  Smart and hilarious, Forget Me Not is about two people giving themselves—and love!—a second chance.